Difficulties in Comprehending Japanese Fukugoudoushi of the Japanese Language Learners from Indonesia - Dwi Puspitosari (Journal of Japanese Language Education and Linguistics, 2023)
Compound verbs, or Fukugoudoushi in Japanese, are unique verbs formed by combining two or more verbs or free morphemes. The Japanese language has around 2,700 compound verbs used daily. According to Morita (1991)'s survey in "Reikai Kokugo Jiten," 11.4% of the documented words are verbs, with compound verbs accounting for 39.29%. Compound verb proficiency presents three hurdles, according to Matsuda (2004). These problems include comprehending the variables that control compound verb combination, distinguishing the nuanced meaning differences between single and compound verbs, and designing effective learning strategies to help achieve compound verb acquisition. In this study, researchers used written assessments, questionnaires, and interviews to determine the factors that affect Fukugoudoushi comprehension and how to remedy them. According to test results, students' difficulty understanding compound verb semantics can be categorized into the following categories:1) Compound verbs encompassing acquired and unacquired information. 2) Verb compounds with different frequency in spoken and written language. 3. Compound verbs for physical or intangible notions. The methods for understanding compound verbs are: Three compound verb interpretation strategies exist. First, understand each verb individually, starting with 1 and then 2. The noun nearest to a compound verb might also indicate its meaning. The second way to interpret compound verbs is to look at the sentence as a whole. Finally, the third method infers compound verb meanings from known verbs.